Perception, Prevalence, and Determinants of Intimate Partner Violence During Pregnancy in Urban Slums of Pune, Maharashtra, India - Jungari, Suresh (Journal of interpersonal violence, 2022)
There is limited evidence on the prevalence and determinants of violence against pregnant women in India. Previous studies were entirely restricted to the violence against women in the reproductive age group. There is lack of evidence about the factors affecting violence against women during pregnancy. Understanding such factors, women’s perception regarding violence during pregnancy and their justification of such violence could manifest an important aspect of violence. Women living in slum communities particularly are victims of violence. In this context, this study intended to examine women’s perception, prevalence of, and factors affecting the violence against women during pregnancy in the slum communities of Pune. A community-based cross-sectional study of 1-year duration was undertaken in urban slums of Pune city, Maharashtra, India. The study participants were women who have delivered 2 years preceding the survey. Using simple random sampling, 500 women were selected from 10 purposively selected slums. House-to-house visits were made and face-to-face interviews conducted using a pretested structured questionnaire. Univariate, bivariate, and logistic regression analyses were applied. The study results show that 15.3% of women have experienced violence during their recent pregnancy. Furthermore, 9.2% of women experienced physical violence, 1.8% sexual violence, and 11.2% psychological violence. Education level of women, husband’s education and alcohol consumption, history of violence in the family, and provision of spurious justification for violence have emerged as some of the leading factors associated with the violence inflicted during pregnancy. Effective interventions at both community and health care settings are needed urgently to reduce the violence inflicted during pregnancy.